Depression in doctors: A bitter pill to swallow - K. Outhoff (South African Family Practice)
At some point in their career, at least a third of doctors suffer personal health problems such as injury, aging, or physical and mental illness, which detract from their ability to function properly and to practice medicine safely. In most, impairment is amenable to intervention, treatment, recovery or resolution. However, some conditions, notably depression, may be overrepresented in the medical profession, under-recognized, stigmatised and undertreated, which may have fatal consequences.